Цінності суспільства глобального ризику та режим декарбонізації - Гарбузова, Д. С. (ХНУРЕ, 2024)
The article is devoted to the development of the concept of "global risk society" and the problems of promoting the international regime of decarbonization. It is proved that the influence of man on nature, the rapid complication of the technological system, the rapid development of the consumer society and the intensity of global connections contribute to an increase in the risk of natural and man-made disasters. The current ecological situation is characterized not only by the limitation and shortage of the main natural resources, but also by a systemic imbalance at the global level. The result of such an imbalance is a constant sense of future danger, which arises not only among experts, but also among all of humanity
Keywords: режим декарбонізації